Rotavirus diarrhoea in under five population in Northern India - Srivastava, Shilpi; Awasthi, Shally; Jain, Amita; Verma, Sheetal; Gupta, Shilpi; Singh, Mastan (Indian Journal of Community Health, 2015)
Background: Infant and childhood diarrhoea due to Rotavirus causes over half a million deaths globally of which an estimated one fifth occur in India alone. Vaccination is being recommended by WHO in most parts of the world. Objective: This study aims at providing estimates of disease burden in the under-five pediatric population and the demographic factors associated with the population affected. Methods: Stool specimens were collected from children suffering from acute diarrhoea and aged between one to five years. Acute diarrhoea was defined as passage of three or more liquid or loose stools per day (or more frequent passage than is normal for the individual, WHO fact sheet). Demographic and clinical information about the patient was collected using a precoded questionnaire. ELISA was used to test stool specimens for presence of antigen of Group A Rotavirus. Chi-square test was used to analyze data. Univariate and multivariate logistic regression models were used. Results: Of the 256 children whose samples were collected over two years 150 were hospitalized and 106 were treated in the community. Rotavirus prevalence was 26% in the hospitalized population and 5.6% in the community. Overall 17.6% (95%CI=12.9-22.3) were positive by ELISA. Conclusion: The risk of rotavirus infection was significantly higher in underweight children (z scores weight for age less than -2 SD (68.9%, OR= 4.76 95%CI=(2.38-9.53), <0.0001) , were severely dehydrated (4.36%, OR=4.36, 95%CI=2.13-8.92, p<0.0001) and had vomiting (40%, OR=0.28, 95%CI=0.15-0.55), p<0.0001).